Pengaruh Pelatihan dan Pengalaman Kerja Terhadap Kinerja Pegawai pada Kantor Sistem Administrasi Manunggal Satu Atap (Samsat) Raba Kota Bima - Elsa Rosali; Firmansyah Kusumayadi; Ikbal Irawan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine whether training and work experience have a significant influence on employee performance at the One-Stop Integrated Administration System Office (SAMSAT) Raba, Bima City. The research instrument used a questionnaire with a Likert scale. The population in this study consisted of all employees at the One-Stop Integrated Administration System Office (SAMSAT) Raba, Bima City, totaling 42 employees, consisting of 14 employees with Civil Servant status (PNS), 2 employees with full-time Government Employees with Work Agreements (P3K) status, and 26 employees with part-time P3K status. The sample in this study consisted of 42 State Civil Apparatus (ASN) employees, including 14 PNS employees, 2 full-time P3K employees, and 26 part-time P3K employees. The sampling technique used was random sampling. Data collection techniques included observation, questionnaires, and literature studies. The data analysis techniques used validity tests, reliability tests, multiple linear regression analysis, classical assumption tests, correlation coefficient tests, determination coefficient tests, t-tests, and f-tests with the assistance of SPSS version 26 for Windows. The results of the study indicate that training has a significant partial effect on employee performance, work experience has a significant partial effect on employee performance, and training and work experience simultaneously have a significant effect on employee performance at the One-Stop Integrated Administration System Office (SAMSAT) Raba, Bima City